Role of Herbal Essential Oil in Cervical Cancer: A Systematic Review - Sah, Shailendra; Kumar, Roshan; Saini, Rita; Patil, Shivanand M. (Journal for Research in Applied Sciences and Biotechnology, 2024)
Cancer of the cervix is a disease that is ubiquitous and frequently severe, and it affects women all over the world. Conventional treatment methods, which include surgical procedures, chemotherapy, and radiation therapy, have been shown to dramatically enhance survival rates; nevertheless, these methods are frequently accompanied with adverse effects and difficulties that might have an influence on the quality of life of a patient. In recent years, there has been a growing interest in the utilisation of essential oils in the cancer treatment and management of cervical cancer. This review offers a comprehensive investigation into the function that various essential oils play in the development of cervical cancer. It also includes insights into the possible advantages of these oils as well as the body of research that has been conducted on them. Additionally, the analysis dives into the future directions and issues that will be faced in this developing industry, with a particular focus on advancements in delivery methods and interesting research areas. For the purpose of enhancing the anticancer qualities of essential oils, the encapsulation of essential oils with solid lipid nanoparticles, the nanoemulsification of essential oils, or the combining of essential oils with conventional treatments have all demonstrated promising results. This review attempts to provide a comprehensive viewpoint, balancing the potential of these natural therapies with the obstacles and issues that need to be addressed. As the employment of essential oils in the treatment or management of cervical cancer continues to develop, this study will attempt to provide a comprehensive perspective. The study will attempt to strike a balance between the potential of these natural treatments and the obstacles and issues that need to be addressed.